2021
DOI: 10.3390/v13030522
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian and Avian Host Cell Influenza A Restriction Factors

Abstract: The threat of a new influenza pandemic is real. With past pandemics claiming millions of lives, finding new ways to combat this virus is essential. Host cells have developed a multi-modular system to detect incoming pathogens, a phenomenon called sensing. The signaling cascade triggered by sensing subsequently induces protection for themselves and their surrounding neighbors, termed interferon (IFN) response. This response induces the upregulation of hundreds of interferon-stimulated genes (ISGs), including an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 384 publications
(516 reference statements)
0
21
0
Order By: Relevance
“…In contrast, DDX21 was reported to inhibit IAV RNA synthesis by interacting with the PB1 subunit of the polymerase [76,77]. The DDX21-PB1 interaction is prevented in part by NS1, impairing DDX21 antiviral effect.…”
Section: Ddx1/ddx21/dhx36mentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, DDX21 was reported to inhibit IAV RNA synthesis by interacting with the PB1 subunit of the polymerase [76,77]. The DDX21-PB1 interaction is prevented in part by NS1, impairing DDX21 antiviral effect.…”
Section: Ddx1/ddx21/dhx36mentioning
confidence: 96%
“…In the context of HIV-1 infection, DDX21 was identified as a binding partner of Rev viral protein, promoting HIV-1 production [75]. In contrast, DDX21 was reported to inhibit IAV RNA synthesis by interacting with the PB1 subunit of the polymerase [76, 77]. The DDX21-PB1 interaction is prevented in part by NS1, impairing DDX21 antiviral effect.…”
Section: Ddx1/ddx21/dhx36mentioning
confidence: 99%
“…ISG20 inhibits the replication of IAV by interacting with viral NP protein and inhibiting viral polymerase activity. [33][34][35] Translation of ISG20 can be regulated by binding miRNA-326 (miR-326) to 3 0 UTR of ISG20 mRNAs. In this regard, Chai et al 23 showed that IAV increases the expression of an interferon-inducible lncRNA termed lnc-ISG20.…”
Section: Lncrnas That Prevent Iav Replicationmentioning
confidence: 99%
“…The inclusion of zinc-finger antiviral protein (ZAP, see Figure 4C), given its ability to recognize RNA and antiviral activity of diverse RNA viruses (including IAV) through depleting vRNAs with high frequencies of CG dinucleotides [91][92][93][94] may also provide deeper host-viral interactions. Aside from the discussed host proteins, understanding restriction factors and their mechanism of action are key to the development of therapeutics and prophylactics [95], as exemplified by the autophagy regulator TBC1D5 which controls IAV replication and promote lysosomal targeting of its M2 protein [96] and a natural variant (D130A) in ANP32B which impairs dimeric influenza virus polymerase formation and viral replication [97].…”
Section: Contribution Of Host Proteinsmentioning
confidence: 99%